Acute and sub-acute toxicity study of a Pakistani polyherbal formulation - Saiqa Ishtiaq; Maida Akram; Sairah Hafeez Kamran; Uzma Hanif; Muhammad Shaharyar Khan Afridi; Sajid-; Atika Afzal; Ayesha Asif; Muhammad Younus; Shehla Akbar (BMC, 2017)
Abstract Background Herbology is the prevailing system among the nationally-accepted alternative or complementary systems of medicine. The system is due to its general and patient-oriented methodology, is widely used in the general population exposing them to the risk of the side effects of the herbal medicines. Method The aim of study was to assess the acute and sub-acute toxicity of the polyherbal formulation Hab-e-Kabad Noshadri tablets. In the acute arm of the study, a single dose of 2000 mg/kg was administered to Swiss Albino mice which were observed for physical symptoms and behavioral changes for 72 h. In sub-acute toxicity study repeated doses of the polyherbal preparation was administered to Wistar rats of both genders, separately. The animals received three doses of polyherbal product (50 mg/kg/day, 100 mg/kg/day and 200 mg/kg/day) for a period of 28 days. On 28th day of experiment, blood sampling of animals was done for hematological and biochemical analysis i.e. liver and renal function parameters, lipid profile and then sacrificed for histopathological examination of liver and kidney. Result There was no morbidity and mortality noticed with single dose administration in acute toxicity study in mice. In sub-acute toxicity study, morphological changes with some damage in liver and kidney tissues of male and female animals were recorded at dose of 100 mg/kg/day and 200 mg/kg/day. Conclusions It was found that prolonged use at higher dose i.e. 200 mg/kg/day of this polyherbal formulation should be avoided and practitioners should cautiously prescribe this formulation in patients with hepatic and renal impairment.